Association between neutrophil/lymphocyte ratio and coronary collateral circulation. Issue 1 (2012) - Çil, Habib; İslamoğlu, Yahya; Yavuz, Celal; Atılgan, Zuhal Arıtürk; Çalışkan, Ahmet; Demirtaş, Sinan; Oylumlu, Mustafa
No abstract available